2009
DOI: 10.1111/j.1540-8159.2009.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

The Undetermined Geometrical Factors Contributing to the Transverse Conduction Block of the Crista Terminalis

Abstract: The CT structural characteristics that may influence its transverse conduction differ between LRA and CS pacing. Steep slope and arborization of the CT are implicated as a geometric factor in its transverse conduction block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The transverse conduction block in the crista terminalis has been reported to be a major determinant in the arrhythmogenesis of CTI-dependent AFL. 26,27 Recent data with UHR showed that the crista terminalis was inconstantly observed during AFL, and that a more posterior line of the block may also be involved in 16 of 22 patients.…”
Section: Cti As a Zone Of Slow Conduction/ Role Of The Crista Terminamentioning
confidence: 99%
“…The transverse conduction block in the crista terminalis has been reported to be a major determinant in the arrhythmogenesis of CTI-dependent AFL. 26,27 Recent data with UHR showed that the crista terminalis was inconstantly observed during AFL, and that a more posterior line of the block may also be involved in 16 of 22 patients.…”
Section: Cti As a Zone Of Slow Conduction/ Role Of The Crista Terminamentioning
confidence: 99%
“…This is thought to be the main pathology behind AFLUT rhythms. However, majority of the cases include structural and electrical abnormalities (similar to AFIB) as the main culprit behind the flutter waves [3335]. One major difference in AFIB and AFLUT is that the thickness of the terminal crest of the atria and its capacity to block transverse conduction are increased in cases of AFLUT compared to AFIB [36,37].…”
Section: Pathophysiologymentioning
confidence: 99%
“…18 In this issue of PACE, Morita and colleagues bring a new piece to the puzzle. 19 As it appears that CT transverse conduction block is rate-and location-dependent, these authors used intracardiac echography to attempt to correlate various geometrical (architectural) parameters of the CT at various level along its course (every 5 mm), to its local transverse conduction properties. This was done at various pacing cycle length from both the anteroinferior right atrium (AIRA) and the proximal coronary sinus (PCS).…”
mentioning
confidence: 99%